2010
DOI: 10.1074/jbc.m110.136895
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Pathogen-associated Molecular Patterns Stimulate Biological Activity of Orthopaedic Wear Particles by Activating Cognate Toll-like Receptors

Abstract: Aseptic loosening of orthopaedic implants is induced by wear particles generated from the polymeric and metallic components of the implants. Substantial evidence suggests that activation of Toll-like receptors (TLRs) may contribute to the biological activity of the wear particles. Although pathogen-associated molecular patterns (PAMPs) produced by Gram-positive bacteria are likely to be more common in patients with aseptic loosening, prior studies have focused on LPS, a TLR4-specific PAMP produced by Gram-nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(127 citation statements)
references
References 60 publications
7
117
1
2
Order By: Relevance
“…Consistent with that view, responses to titanium wear particles that involve TLR2 or TLR4 have been shown to require adherence of cognate PAMPs to the wear particles [37]. Those results are strong, albeit indirect, evidence that the alarmins are not sufficient to activate those TLRs in the absence of PAMPs in the cell culture and murine models that were studied (Fig.…”
Section: Toll-like Receptorssupporting
confidence: 64%
See 1 more Smart Citation
“…Consistent with that view, responses to titanium wear particles that involve TLR2 or TLR4 have been shown to require adherence of cognate PAMPs to the wear particles [37]. Those results are strong, albeit indirect, evidence that the alarmins are not sufficient to activate those TLRs in the absence of PAMPs in the cell culture and murine models that were studied (Fig.…”
Section: Toll-like Receptorssupporting
confidence: 64%
“…Moreover, it has recently been reported that human TLR4 can be activated by cobalt or nickel ions [88,110], both of which can be released by corrosion of cobaltchromium implants [39]. Functional studies have shown that deletion of TLR2 and/or TLR4 in murine systems substantially reduces the in vitro and in vivo responses to titanium [8,37], UHMWPE [40], cobalt-chromium [85], and hydroxyapatite [34] particles. Moreover, similar results have also been obtained for deletion of the myeloid differentiation primary response gene (MyD88) with both PMMA and cobalt-chromium particles [82,85].…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…Furthermore, cobalt ions have been shown to directly bind to and activate TLR4 signalling [92][93][94]. Exo-or endogenous DAMPs can bind to wear particles surfaces and mediate particle-induced inflammation via TLR signalling [95][96][97][98]. As discussed above, TLR signalling, especially via TLR4, is one of the cues that can induce M1-like macrophage phenotype.…”
Section: Macrophage Activation and Polarization In Aseptic Looseningmentioning
confidence: 99%
“…An important role in the transduction of hypoxic signal to bone-implant interface may be played by osteocytes via increased expression of HIF and osteopontin leading eventually to osteocyte-induced osteoclastic bone resorption (Gross et al 2005). Activation of PRRs by occurrence of PAMPs in periprosthetic tissues can distort local tissue homeostasis at any time postoperatively (Greenfield et al 2010). PRRs have a strong potential to trigger inflammation via several pathways including differentiation of more aggressive M1 and M17 macrophages, multinuclear foreign body giant cells, osteoclasts and granulomas (Anderson et al 2008).…”
Section: Control Of Prosthesis-related Inducersmentioning
confidence: 99%
“…on wear debris particles. Some researchers have demonstrated that i) PAMPs adhere to the particles; ii) adherent PAMPs increase significantly the biological response to the particles; iii) PAMPs do this by activating their PRRs (Greenfield et al 2010). In addition, particles deliberated from THA are coated immediately with serum proteins creating a protein-particle complex that may result in a damage/danger-associated molecular pattern picture irrespective of endotoxin (Sun et al 2003).…”
Section: Hierarchy Of Immune Reactions To Prosthetic Wear Particles (mentioning
confidence: 99%